2013
DOI: 10.4238/2013.march.11.14
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ERK1/2 signaling in proliferation of eight liver cell types during hepatic regeneration in rats

Abstract: ABSTRACT. It has been well established that ERK1/2 signaling, often subdivided into nine types of pathways, can regulate the hepatocyte proliferative response during liver regeneration. However, the effect of ERK1/2 signaling on the proliferation of other hepatic cell types remains unclear. We isolated and purified 8 liver cell types at 10 time points after 2/3 hepatectomy in adult rats. For each cell type, mRNA expression changes for ERK1/2 signaling-involved genes were monitored up to 168 h, using microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
(14 reference statements)
3
10
0
Order By: Relevance
“…It has also been reported that ERK1/2 signaling pathway can positively regulate proliferation of LSECs [33] and the phosphorylation of ERK1/2 increases HIF-1a expression, thus promoting the production of classical angiogenic factors such as VEGF [34]. Our present study indicated that overexpression of KLF2 inhibited the activation of p-ERK1/2, and after blocking ERK1/2 with the specific inhibitor PD98059, the inhibitory effect of KLF2 on LSEC proliferation and migration was also blocked.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It has also been reported that ERK1/2 signaling pathway can positively regulate proliferation of LSECs [33] and the phosphorylation of ERK1/2 increases HIF-1a expression, thus promoting the production of classical angiogenic factors such as VEGF [34]. Our present study indicated that overexpression of KLF2 inhibited the activation of p-ERK1/2, and after blocking ERK1/2 with the specific inhibitor PD98059, the inhibitory effect of KLF2 on LSEC proliferation and migration was also blocked.…”
Section: Discussionsupporting
confidence: 60%
“…The ERK1/2 signaling pathway is known to play an important role in endothelial proliferation and migration, which are two essential procedures in the process of angiogenesis [33]. It has also been reported that ERK1/2 signaling pathway can positively regulate proliferation of LSECs [33] and the phosphorylation of ERK1/2 increases HIF-1a expression, thus promoting the production of classical angiogenic factors such as VEGF [34].…”
Section: Discussionmentioning
confidence: 98%
“…Hepatocytes are the primary cells to enter the cell cycle and undergo proliferation. Hepatocytes produce mitogenic signals for other types of liver cells, and every mediator drives the downstream cascades, which transfer hepatocytes from the quiescent state to the cell cycle [29].TNF-α/NF-ÎșB, IL-6/signal transducer and activator of interpretation 3 (STAT3), phosphatidylinositol-3-kinase (PI3K)/Akt, HGF/HFG receptor (cMet), and extracellular signal-regulated kinase 1/2 (ERK1/2) are all important pathways involved in liver recovery [30]. The aforementioned mechanisms clarify the role of PRP in improving liver fibrosis because of its high content of growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…This has made the liver an excellent model for studying organ regeneration [1][2][3][4] . The regenerative process is typically divided into the priming, proliferating and termination phases, occurring approximately at first, third and seventh days after resection, respectively 5 . Clinically, the regenerative ability of livers provides the cornerstone of many surgical treatments for liver diseases; resection of diseased portions seems to improve survival 6 .…”
mentioning
confidence: 99%